Chapter 6 Partners into Competitors Divisive Democracy and Conflicting Conceptions of Citizenship - Štiks, Igor (Bloomsbury Academic, 2015)
The clash between civic and ethnic solidarity as well as diverse understanding of whom should be loyal to whom and who belong together turned decisive at the moment when the multi-party majority democracy was introduced in the Yugoslav republics. Democratic participation and political belonging clashed in Yugoslavia at the junction of Yugoslav citizenship, republican citizenship and ethnic membership. Yugoslavia's initial democratization eventually exacerbated inter-republic and inter-ethnic conflicts which had been meticulously nurtured and controlled by those nationalist elites who were attempting to, by multi-party elections, accede to power or stay in power. In this context, messages sent from the West underscoring the importance of state consolidation for successful democratization did not pressure regional actors to redefine or reform their ethnically heterogeneous states towards greater pluralism. They reinforced the idea that a truly functional state could only be an ethnically homogenized nation-state. In multinational socialist federations, it ended up promoting ethnically based political communities in opposition to the existing civic-legal political communities at the republican level as basis for democracy. This chapter argues that this ethnocentric vision of citizenship immediately challenged the existing social realities and institutional settings, put in question the borders between the republics, and opened the doors for violence and war. In his book States and Power in Africa: Comparative Lessons in Authority and Control, Jeffrey Herbst describes the conflicts between the Zulu and early Dutch settlers over their opposing conceptions of sovereignty over territory and people. The Zulu believed that their political authority extended wherever people had pledged obedience to their king regardless of the territory where they happened to be. Also, 'the Zulu believed that they could let the whites settle on land without giving up ownership', whereas for the European whites, occupation over a certain territory also meant the ownership of that territory and control of the people that happened to be there (2000: 40-41). Extrapolated from its colonial context in which the Dutch colonizers wanted to absolutely dominate the colonized and take their land, the story could be interpreted as a clash between the conception of a political community based on ethnic, cultural, hereditary or maybe also declaratory loyalty and solidarity, regardless of existing political boundaries and polities in which the members of this community live, and a political community based on loyalty to the authorities governing a territory where one lives and, ideally, on solidarity with all those who happen to be on that territory under the same authorities. Modern states in reality often combine these two principles in a particular way: they often claim that their citizens or their ethnic kin abroad are bound to their polity and thus expect a loyalty and sometimes exercise an influence on diaspora members (who, in turn, are often interested in meddling in political affairs of the 'old country'), but, internally, they always insist on undivided loyalty of the population they govern. Even further from its original South African situation, the clash between what we can generally call civic and ethnic solidarity, as well as different understandings of whom should be loyal to whom and who belonged together, turned crucial during the last years of Yugoslavia and decisive at the moment when the multi-party majority democracy was introduced in its republics.